2006
DOI: 10.1016/j.adolescence.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent risk behaviors and religion: Findings from a national study

Abstract: Too few studies have assessed the relationship between youth risk behaviors and religiosity using measures which captured the varied extent to which youth are engaged in religion. This study applied three measures of religiosity and risk behaviors. In addition, this study ascertained information about youths' participation in religious activities from a parent or caretaker. Based on a national random sample of 2,004 teens (ages 11-18), this study indicates that youth perceive religion as important, are active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
236
5
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(281 citation statements)
references
References 42 publications
27
236
5
13
Order By: Relevance
“…Two items measured aggressive behaviours; namely, fighting verbally [36] and physically [9] with peers. Four items measured antisocial activities; namely, skipping class [37], vandalising property [37], stealing or shoplifting [18], and breaking school rules for no specific reason. Four items measured substance-related risks; namely, smoking cigarettes [15,20], drinking alcohol with the intention of becoming drunk [26,36,37], smoking marijuana [20], and taking ecstasy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two items measured aggressive behaviours; namely, fighting verbally [36] and physically [9] with peers. Four items measured antisocial activities; namely, skipping class [37], vandalising property [37], stealing or shoplifting [18], and breaking school rules for no specific reason. Four items measured substance-related risks; namely, smoking cigarettes [15,20], drinking alcohol with the intention of becoming drunk [26,36,37], smoking marijuana [20], and taking ecstasy.…”
Section: Methodsmentioning
confidence: 99%
“…Four items measured antisocial activities; namely, skipping class [37], vandalising property [37], stealing or shoplifting [18], and breaking school rules for no specific reason. Four items measured substance-related risks; namely, smoking cigarettes [15,20], drinking alcohol with the intention of becoming drunk [26,36,37], smoking marijuana [20], and taking ecstasy. Three items measured road safety; namely, riding a bicycle without a helmet [34], traveling in a car without a seat-belt [26,38], and traveling in a car where the driver was unsafe [26,36,38], with examples of speeding or driving while intoxicated provided.…”
Section: Methodsmentioning
confidence: 99%
“…Dez anos depois, seguindo os mesmos padrões metodológicos, esse fato também se verificou em um estudo realizado entre adolescentes que viviam nos Estados Unidos (Sinha et al, 2006).…”
Section: Aspectos Geraisunclassified
“…Although different religious denominations have different effects on people's attitudes towards risk, the simple fact of being religious seems to increase the likelihood of risk aversion (Noussair, Trautmann, Van de Kuilen, & Vellekoop, 2013). The importance attributed to religion and participation in religious activities are also consistently associated with reduced risky behaviors (Sinha, Cnaan, & Gelles, 2007). Along similar lines, several studies have shown that, when primed with the idea of god or other spiritual terms, individuals are more likely to be prosocial (Shariff & Norenzayan, 2007) and less likely to engage in immoral actions such as cheating in an exam (Shariff & Norenzayan, 2011).…”
mentioning
confidence: 99%